2012
DOI: 10.1186/1750-2187-7-1
|View full text |Cite
|
Sign up to set email alerts
|

The adaptor protein p62/SQSTM1 in osteoclast signaling pathways

Abstract: Paget's disease of bone (PDB) is a skeletal disorder characterized by focal and disorganized increases in bone turnover and overactive osteoclasts. The discovery of mutations in the SQSTM1/p62 gene in numerous patients has identified protein p62 as an important modulator of bone turnover. In both precursors and mature osteoclasts, the interaction between receptor activator of NF-κB ligand (RANKL) and its receptor RANK results in signaling cascades that ultimately activate transcription factors, particularly NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 78 publications
(115 reference statements)
1
38
0
Order By: Relevance
“…MAPK9 encodes a kinase involved in signal transduction pathways that is required for late-stage differentiation of osteoblasts and overexpression of which causes increased mineral deposition in bone [Matsuguchi et al, 2009]. Additional genes in the region may also play roles in bone formation, including HNRNPAB [Fomenkov et al, 2003], ADAMTS2 [Bar-Yosef et al, 2008] and SQSTM1 [Chamoux et al, 2009;McManus and Roux, 2012], although there is insufficient literature to support a direct mechanism of a copy gain of these genes. Finally, it is possible that subject 8's craniosynostosis is secondary to her microcephaly, and duplication of one or more genes distal to NSD1 causes microcephaly, as opposed to causing craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK9 encodes a kinase involved in signal transduction pathways that is required for late-stage differentiation of osteoblasts and overexpression of which causes increased mineral deposition in bone [Matsuguchi et al, 2009]. Additional genes in the region may also play roles in bone formation, including HNRNPAB [Fomenkov et al, 2003], ADAMTS2 [Bar-Yosef et al, 2008] and SQSTM1 [Chamoux et al, 2009;McManus and Roux, 2012], although there is insufficient literature to support a direct mechanism of a copy gain of these genes. Finally, it is possible that subject 8's craniosynostosis is secondary to her microcephaly, and duplication of one or more genes distal to NSD1 causes microcephaly, as opposed to causing craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the intensity of autophagy flux activity, degradation of p62/SQSTM1, the substrate of autophagy [32], and lipidation of LC3 (conversion of LC3-I into LC3-II) were analyzed by western blot. Dex led to down-regulated p62 and up-regulated LC3-II which signified stronger autophagy flux activity (Fig.…”
Section: Dex-induced Ros Led To Autophagy In Osteoclast Precursorsmentioning
confidence: 99%
“…Because of its unique binding to ubiquitinated proteins together with its ability to bind LC3, p62 has been demonstrated to be an important receptor protein for selective autophagic clearance of ubiquitinated protein aggregates and organelles 5, 9 . The importance of the UBA domain of p62 has also been underscored by the findings that mutations of the UBA domain are frequently associated with familial and sporadic Paget’s disease of bone, which is a chronic and metabolic disorder characterized by increased bone turnover 3941 . It is well known that RANKL and its receptor RANK play an important role in regulating osteoclast differentiation, activity, and survival by activating NF-κB 6 .…”
Section: Structure and Multiple Functions Of P62mentioning
confidence: 99%
“…It has been suggested that p62 forms a complex with TRAF-6 and aPKC, which is critical for RANKL-induced NF-κB activation 6, 42, 43 . Mutations in the UBA domain results in loss of UBA function and also activate TRAF6–NF-kB signaling, which results in increased osteoclastogenesis 8, 39, 44 . p62 KO mice also show a similar phenotype reminiscent of Paget’s disease with impaired NF-κB activation 6 , further supporting that p62 is an important mediator regulating bone homeostasis.…”
Section: Structure and Multiple Functions Of P62mentioning
confidence: 99%